Biomechanical principles of rehabilitation of the young tennis player - Micheo, W. (2002)
Rehabilitation is defined as the return to normal form and function. In athletes, this requires returning to a high level of skilled function. In this population, the absence of symptoms is not equivalent to normal function. The young athlete has special characteristics, including ligamentous laxity, an immature musculoskeletal system and lack of co-ordination, which may predispose them to injury associated with participation in sports. Tennis is a sport that places significant demands on the upper extremities, lower extremities, and the spine of the growing athlete. Rehabilitation of the injured athlete requires an accurate diagnosis based on the patient's symptoms, physical examination and demands of the sport, leading to a specific treatment that addresses the entire kinetic chain. The diagnosis should follow the musculoskeletal injury model, which identifies a symptoms complex, a tissue injury complex and a functional deficits complex. Symptoms commonly addressed in the young tennis player include pain, weakness and instability. Anatomic sites of tissue injury in this population include the rotator cuff, posterior elements of the lumbar spine and the patello-femoral joint. Functional deficits that should be addressed in the tennis player include inflexibility, muscle imbalance and loss of accuracy and placement in the serve, as well as ground strokes. Rehabilitation is divided into the acute, recovery, and maintenance phases. The acute phase should address tissue injury and the patients' symptoms. The recovery phase should address tissue injury and overload, allowing the athlete return to normal strength, flexibility and functional activities. The maintenance phase should address biomechanical deficits while working on sports-specific performance and the prevention of recurrent injury. The young athlete is not a small adult. Injury results from the specific demands of the sport as well as the characteristics of the individual young athlete. These two aspects need to be addressed for an effective management and rehabilitation programme.